Suppression of Inflammatory Mediators by Cruciferous Vegetable-Derived Indole-3-Carbinol and Phenylethyl Isothiocyanate in Lipopolysaccharide-Activated Macrophages. (13th April 2010) - Tsai, Jo-Ting; Liu, Hui-Ching; Chen, Yue-Hwa
Abstract : This study was aimed to examine the effects of indole-3-carbinol (I3C) and β -phenylethyl isothiocyanate (PEITC), bioactive components present in cruciferous vegetable, on the production of inflammatory mediators, including nitric oxide (NO), tumor necrosis factor-α (TNF-α ) and interleukin-10 (IL-10), in lipopolysaccharide- (LPS-) stimulated RAW 264.7 macrophages. Possible mechanisms of the NO-inhibitory effects were also explored. The results indicated that I3C and PEITC inhibited NO production, and this suppression was associated with decreased production of TNF-α and IL-10 by activated macrophages. In addition, I3C suppressed NO production even after the inducible nitric oxide synthase (iNOS) protein had been produced, but such an inhibitory effect was not observed in cells treated with PEITC. Furthermore, both compounds reduced the NO contents generated from an NO donor in a cell-free condition, suggesting that the increased NO clearance may have contributed to the NO-inhibitory effects. In summary, both I3C and PEITC possessed antiinflammatory effects by inhibiting the productions of NO, TNF-α, and IL-10, although the NO-inhibitory effects may have involved in different mechanisms.